2003
DOI: 10.1007/s00277-002-0603-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thrombophilia detected in southern Taiwanese patients with venous thrombosis

Abstract: In order to analyze the incidence of thrombophilia in southern Taiwan, we studied the prevalence of antithrombin (AT), protein C (PC), and protein S (PS) deficiencies, the prevalence of factor V Leiden mutation, and the presence of acquired lupus anticoagulant (LA) and anticardiolipin antibody (ACA) in 56 patients < or =65 years old with deep venous thrombosis (DVT). Of 56 patients, 30 were male, 26 female, and the mean age of the patients was 43 years (18-65 years). None had factor V mutation or activated PC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…In our study, the prevalences of a LA (9.1%), antithrombin III deficiency (3.1%), activated protein C resistance (18%) and mutation 20210A of the prothrombin gene (9.3%) were similar to those reported in the literature; i.e., respectively 4% to 16% (11,12,16,20); 1.4% to 7.1% (14)(15)(16)(17)(21)(22)(23); 5% to 40% (11,13,16,17,19,22,(24)(25)(26)(27), and 4% to 18% (11,13,19,(25)(26)(27)(28). We found a relatively high prevalence of protein S deficiency (12%) usually not noticed in our white countries, quite similar to those observed in Asia (15,21,22,29).…”
Section: Efficiency Of Thrombophilia Screening 247supporting
confidence: 88%
“…In our study, the prevalences of a LA (9.1%), antithrombin III deficiency (3.1%), activated protein C resistance (18%) and mutation 20210A of the prothrombin gene (9.3%) were similar to those reported in the literature; i.e., respectively 4% to 16% (11,12,16,20); 1.4% to 7.1% (14)(15)(16)(17)(21)(22)(23); 5% to 40% (11,13,16,17,19,22,(24)(25)(26)(27), and 4% to 18% (11,13,19,(25)(26)(27)(28). We found a relatively high prevalence of protein S deficiency (12%) usually not noticed in our white countries, quite similar to those observed in Asia (15,21,22,29).…”
Section: Efficiency Of Thrombophilia Screening 247supporting
confidence: 88%
“…A recent study in the Netherlands showed that the absolute thrombotic risks in patients with PC, PS, or AT deficiency were much higher than those in patients with factor V Leiden or prothrombin 20210A 12. This finding, along with the prevalence of anticoagulant deficiencies seen in the present study and in other studies from Asian countries,15,16 indicates that tests for HT and risk stratification according to the presence of HT are important in Asian patients with VTE. A study in Taiwan demonstrated that thrombotic risks for PC or PS deficiency are higher than those for AT deficiency or PLG deficiency 9.…”
Section: Discussionsupporting
confidence: 66%
“…Up to 52% of patients with iPE had PC, PS, AT, or PLG deficiency. Other recent studies in Asian countries reported that the prevalence of HT in all-cause DVT were 28.3% and 32.1% in Japan and Taiwan, respectively 15,16. Although the prevalence of HT in idiopathic VTE was not known well, a study reported that 67% of patients with idiopathic DVT had one positive marker for thrombophilia including factor V Leiden and prothrombin mutations as well as PC, PS, and AT deficiencies 17.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] These results correspond with reports from other Asian countries. [12][13][14][15][16] Other than genetic polymorphism, the difference in fibrinolytic activity, 17 lifestyle factors, the prevalence of obesity as well as psychosocial stress also affect the incidence of thromboembolism. 18 Homocysteine has been found to be a risk factor, in both adults and children, for the development of cardiovascular disease and venous and arterial thrombosis including stroke.…”
mentioning
confidence: 99%